Pengembangan Video Animasi dan Game Open The Boks Berbasis IT di MTS Islamiyah Palangka Raya - Winda Winda; Anisa Anisa; Abdul Aziz; Dewi Aulia; Muhammad Hasan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Learning is still teacher-focused, students often feel bored in learning, especially learning fiqh, therefore this study aims to increase student activeness in fiqh learning at MTs Islamiyah through the development of learning media in the form animation videos and games “Open the Box”. Learning that still focuses on the teacher causes students to feel bored and lackluster. By utilizing technology, this research develops interesting interactive media to support the teaching and learning process. The method used is research and development (R&D) with the ADDIE model. The results showed that the use animated videos and educational games can increase student motivation and engagement in fiqh learning.